Jetting from cavitation bubbles in viscous and confined liquids - Zeng, Qingyun (Nanyang Technological University, 2020)
Rapidly expanding and shrinking bubbles can produce high-speed jets that can clean nearby surfaces or deliver drugs into tissue and cells by applying shear stress. In this thesis, we use high-speed photography and numerical techniques to resolve the spatio-temporal distribution of shear stress. Short-lived but extremely high stresses of 100kPa are found in simulations due to the spreading of the jet onto the boundary. By confining the bubble within a narrow gap consisting of two rigid plates the jet speed and direction can be altered and an intriguing competition between viscous forces and inertia is resolved. When the bubble is confined within a viscous droplet jetting is observed too, but created through the spherical Rayleigh-Taylor instability. Stability analysis and numerical simulations demonstrate the working mechanism for aqueous liquids as well as for liquid metals. The later droplets are used for extreme UV production in the semiconductor industry.